THE ROLE OF SOCIAL ENVIRONMENT IN THE TRAINING OF HONEST AND LOYAL PERSONNEL - Tojiboyev Sarvar (Scholar Express Journals, 2022)
This article analyzes fair social issues in training honest and loyal staff. As long as the consepts of honesty and loyalty in human life and ideas abaut role of the state development will be analyzed in detail.
Keywords: Honest; loyalty; haram; coruption justice and conscience